PRINSIP PERLINDUNGAN HUKUM TERHADAP DEBITUR YANG TELAH LUNAS KREDIT - Yasinta Vitra Rahma Dewi (Universitas Muhammadiyah Ponorogo, 2023)
There is a very big need for an entity, namely a house, a bank and a developer or often called a developer working together to provide houses for the community. In order to accelerate this goal, the Bank often gives concessions to developers, namely they can cooperate even though the legality of the project has not been completed. In the end, it is consumers or debtors who become victims when they have paid off their credit. The legal research used is juridical normative. The results of the analysis show that in general, protection for customers at the bank can be done through implicit protection or explicit protection. The author concludes that the developer's responsibilities have not been specifically regulated in the UUPK or the Housing Law, because the UUPK only regulates the responsibilities of business actors briefly and not very clearly. Meanwhile, the Housing Law does not regulate developers at all, so developers are free from responsibility. Even though there is a responsibility arrangement in UUPK, the developer has not implemented it properly. The developer is obliged to immediately complete the responsibility for the legality of housing that has been credited to the debtor by submitting it to the Bank, so that the bank can legally provide it to the debtor who has paid off the credit, in accordance with the legal protection provided by the government, which has been established in Law Number 8 of 1999 concerning Consumer Protection (UUPK) Article 1.